2014
DOI: 10.1186/1471-2407-14-292
|View full text |Cite
|
Sign up to set email alerts
|

A role for PAX8 in the tumorigenic phenotype of ovarian cancer cells

Abstract: BackgroundPAX8 is a member of the paired box (Pax) multigene family of transcription factors, which are involved in the developmental and tissue-specific control of the expression of several genes in both vertebrates and invertebrates. Previously, several studies reported that PAX8 is expressed at high levels in specific types of tumors. In particular, PAX8 has been recently reported to be conspicuously expressed in human ovarian cancer, but the functional role of PAX8 in the carcinogenesis of this type of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…E-cadherin was not tested in this system as OSE cells lack expression of E-cadherin [20]. Fibronectin is associated with both EMT and migration, and was analyzed by Di Palma and colleagues in their study of PAX8 in SV40 immortalized human IOSE 80 cells [19]. N-cadherin and Fibronectin protein levels were significantly increased in MOSE-PAX8 cells compared to MOSE-Neo control (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin was not tested in this system as OSE cells lack expression of E-cadherin [20]. Fibronectin is associated with both EMT and migration, and was analyzed by Di Palma and colleagues in their study of PAX8 in SV40 immortalized human IOSE 80 cells [19]. N-cadherin and Fibronectin protein levels were significantly increased in MOSE-PAX8 cells compared to MOSE-Neo control (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Despite its ubiquitous expression and role in other tumor types, little is known about what PAX8 regulates in HGSC. Previous research has shown that PAX8 knockdown in HGSC leads to apoptosis as well as an increase in migration, anchorage independent growth, and tumor suppression [18, 19]. The pathways involved in these phenotypic changes, however, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PAX8 is the single most differentially expressed gene when comparing ovarian cancer cell lines with all other cancer cell lines in the Cancer Cell Line Encyclopedia (24). Loss of PAX8 in most, but not all, serous ovarian cancer cell lines leads to apoptosis and decreased tumorigenicity, while cancer cell lines from other organ sites are unaffected (24, 33). Together, these findings have led to substantial interest in PAX8 as a lineage-defining gene for MĂŒllerian cancers in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by functional evidence showing that PAX8 knockdown in ovarian carcinoma cell lines induces growth arrest, apoptosis, and decreases tumorigenesis [14-16]. The observation of PAX8 expression in fallopian tube secretory epithelial cells (FTSECs) and in many CICs but not OSECs could suggest that the epithelial lining of CICs is derived from the fallopian tube and that most, if not all HGSOCs likely originate from FTSECs.…”
Section: Introductionmentioning
confidence: 88%